2014
DOI: 10.1051/parasite/2014036
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan parasite infection in the swordfish,Xiphias gladius, from the Mediterranean Sea and comparison with Atlantic populations: implications for its stock characterization

Abstract: Thirteen parasite taxa were identified in the Mediterranean swordfish by morphological and genetic/molecular methods. The comparison of the identified parasite taxa and parasitic infection values observed in the Mediterranean swordfish showed statistically significant differences with respect to those reported for its Atlantic populations. A stepwise Linear Discriminant Analysis of the individual fish examined showed a separation among three groups: one including fish from the Mediterranean Sea (CTS, STS, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 55 publications
1
25
1
Order By: Relevance
“…This was, for instance, the case with the larval Anisakis spp. identified in samples of M. merluccius (Mattiucci et al 2004), Trachurus trachurus (Mattiucci et al 2008) and X. gladius (Mattiucci et al 2014 b ). In addition, among the other molecular markers used for Anisakis detection (Mattiucci et al 2014 a ), the high substitution rate of the mtDNA cox 2 sequences found so far in Anisakis spp.…”
Section: Current Methodologies Used For the Identification Of Meditermentioning
confidence: 99%
See 1 more Smart Citation
“…This was, for instance, the case with the larval Anisakis spp. identified in samples of M. merluccius (Mattiucci et al 2004), Trachurus trachurus (Mattiucci et al 2008) and X. gladius (Mattiucci et al 2014 b ). In addition, among the other molecular markers used for Anisakis detection (Mattiucci et al 2014 a ), the high substitution rate of the mtDNA cox 2 sequences found so far in Anisakis spp.…”
Section: Current Methodologies Used For the Identification Of Meditermentioning
confidence: 99%
“…
Fig. 3. The case study of stock assessment of a large pelagic fish species, the swordfish Xiphias gladius from the Mediterranean Sea and Atlantic Ocean, as inferred from biological data, biomarkers (parasites) and the genetic datasets (allozymes) of the same fish populations (data from Garcia et al 2011; Mattiucci et al 2014 b ). (A) Relative proportions of the Anisakis spp.
…”
Section: Case Studies Of Fish Stock Identification In the Mediterranementioning
confidence: 99%
“…Ascaridoid nematodes, including species of Anisakidae, can be pathogenic for humans when consumed in raw fish and can cause massive economic losses for commercial fisheries (Chai, Murrell, & Lymbery, ). Species of Hysterothylacium of the family Rhapidascarididae are one of the most abundant and diverse groups of fish‐parasitizing marine ascaridoids, with a worldwide marine distribution encompassing the North Atlantic, Mediterranean Sea, Pacific Ocean, and Australian, Chinese and South American marine waters (Bruce, Adlard, & Cannon, ; Klapper, Kochmann, O'Hara, Karl, & Kuhn, ; Li, Gibson, & Zhang, ; Mattiucci et al., ; Pekmezci, Yardimci, Onuk, & Umur, ; Shamsi, Gasser, & Beveridge, ; Torres & Soto, ; Zuo et al., ). They are frequently found in edible fish in Spanish Mediterranean and Atlantic waters, including sardine, blue whiting, anchovy and horse mackerel (MacKenzie et al., ; Madrid, Galán‐Puchades, & Fuentes, ; Rello, Adroher, Benítez, & Valero, ; Rello, Adroher, & Valero, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hysterothylacium constitutes a large number of described species, approximately 70, which have been recorded in marine fishes worldwide (Li, Gibson et al., ; MacKenzie et al., ; Pekmezci et al., ; Shamsi et al., ). In Mediterranean and North‐East Atlantic waters, H. aduncum (Rudolphi, 1802) is the most frequently reported species in many teleost fishes, but other species such as H. fabri (Rudolphi, 1819) Deardorff & Overstreet, 1980; H. corrugatum Deardorff & Overstreet, ; H. incurvum (Rudolphi, 1819) Deardorff & Overstreet, 1980; and H. petteri Sheenko, 1991 have also been recorded (Amor, Farjallah, Merella, Said, & Slimane, ; MacKenzie et al., ; Mattiucci et al., ; Ternengo, Levron, Mouillot, & Marchand, ). Up to 17 Hysterothylacium larval morphotypes have been described, based mainly on the anterior digestive tract and the caudal end of larvae, the first description in Australian marine waters being by Cannon ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation